Acrosin is essential for sperm penetration through the zona pellucida in hamsters - Hirose, Michiko; Honda, Arata; Fulka, Helena; Tamura-Nakano, Miwa; Matoba, Shogo; Tomishima, Toshiko; Mochida, Keiji; Hasegawa, Ayumi; Nagashima, Kiyoshi; Inoue, Kimiko; Ohtsuka, Masato; Baba, Tadashi; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
During natural fertilization, mammalian spermatozoa must pass through the zona pellucida before reaching the plasma membrane of the oocyte. It is assumed that this step involves partial lysis of the zona by sperm acrosomal enzymes, but there has been no unequivocal evidence to support this view. Here we present evidence that acrosin, an acrosomal serine protease, plays an essential role in sperm penetration of the zona. We generated acrosin-knockout (KO) hamsters, using an in vivo transfection CRISPR/Cas9 system. Homozygous mutant males were completely sterile. Acrosin-KO spermatozoa ascended the female genital tract and reached ovulated oocytes in the oviduct ampulla, but never fertilized them. In vitro fertilization (IVF) experiments revealed that mutant spermatozoa attached to the zona, but failed to penetrate it. When the zona pellucida was removed before IVF, all oocytes were fertilized. This indicates that in hamsters, acrosin plays an indispensable role in allowing fertilizing spermatozoa to penetrate the zona. This study also suggests that the KO hamster system would be a useful model for identifying new gene functions or analyzing human and animal disorders because of its technical facility and reproducibility.
Keywords: acrosin; interakce spermie a vajíčka; Male; akrozom; akrosin; hamster; fertilization; Spermatozoa; mužské pohlaví; zona pellucida; genový knockout; Sperm-Ovum Interactions; Fertilization in Vitro; fertilizace in vitro; Acrosome; Cricetinae; Animals; Gene Knockout Techniques; ženské pohlaví; zvířata; spermie; Zona Pellucida; Acrosin; Female; křečci praví